Proportionate Atomism: Solving the Problem of Isomorphic Variants in Plato’s Timaeus - Schroeder, Lea Aurelia (Phronesis, 2023)
The principles governing elemental composition, variation, and change in Plato’s Timaeus appear to be incompatible, which has led commentators to prioritize some of the principles to the exclusion of others. Call this seeming incompatibility the problem of isomorphic variants. In this paper, I develop the theory of proportionate atomism as a solution to this problem. Proportionate atomism retains the advantages of rival interpretations but allows the principles of material composition, variation, and change to combine into an internally coherent and explanatorily powerful atomic physics.